ANALISIS SISTEM KELISTRIKAN PADA LABORATORIUM CENTRAL SERVICE KUALA NAMU - Ginting, Estrada; Fahreza, Muhammad; Dalimunthe, Muhammad Erpando (Politeknik Harapan Bersama Tegal, 2024)
Kuala Namu Central Service Laboratory is a laboratory that provides service-based services for electrical and electronic equipment specifically at kuala namu airport equipment. This laboratory uses a lot of laboratory equipment that uses electrical energy. The purpose of this study is to analyse the electrical system on electrical power consumption in the Kuala Namu Central Service Laboratory as well as conduct an analysis between the electrical system of the Kuala Namu Central Service Laboratory with the General Requirements for Electrical Installation and SPLN. Based on the calculation results in the discussion results obtained total power consumption of equipment around 86,637.30 W, from the measurement of operating power of 82,606.66 W. While according to the simulation results using DIg SILENT Power Factory 15.1 .7, the power is 82,604.95 W. The percentage of transformer loading is obtained at 44.08%, this already includes loading according to SPLN standards, while the percentage of generator loading is 89.496% which is declared overloaded. In the simulation results the transformer is 44.08% and the generator is 89.5%. The type of conductor and safety installed as well as the grounding resistance in the building has met the PUIL (General Requirements for Electrical Installation) standard. The grounding resistance of the CPS laboratory building is 2.6 Ω (5 Ω).